Ólbos: uma discussão axiológica nas histórias de Heródoto - Ribeiro, Tatiana Oliveira (2005)
Herodotus of Halicarnassus redeemed the barbarian otherness from the current extreme portraits of unhuman savagery and Greek identity. Acknowledging the Barbarians as having other nómoi, Herodotus points out the cultural differences among peoples, grounding his own propositions in the collected data he shapes, increases and recreates. One of those data is the semantic variation around the concept of ólbos. This Dissertation aims to discuss this Herodotian parameter from its textual occurrences at I, 26-92, the passage known as “Cresus lógos”, a part of the “Lydian lógos”. The research has also focused some occurences of the word ólbos in Greek Literature production untill the V century B.C. in oder to inquire into its efficiency, through its discursive contexts, as an axiological scale defining the Barbarian cultures directions according to what is meant to be the Herodotian perspective. Although it establishes an otherness-oriented point of view, such a perspective is also guided by the delimitation of Athenian ethics values and, for instance, by the purposes of Solon's character acting as a fortress of the democratic system.